POMD12 Visual cue "walking glasses" may aid gait in Parkinson's disease. Issue 11 (22nd October 2010) - McAuley, J; Daly, P; Curtis, C
Abstract : Gait disturbance is an almost universal complaint suffered by PD patients as they inevitably progress to the more severe stages of the disease. This can be partially corrected by external cues guiding placement of each step. "Walking glasses", spectacles that present the patient with visual cues to aid walking without necessitating marking the floor or using a walking stick, have been used with varying degrees of success. We explored the use of a novel design of walking glasses that provide flexibility of visual and auditory cueing and would be very cheap to mass-produce. Performance was measured by timing 15 Parkinson's disease patients' walking over a "real-life" predefined 30 m course using different patterns of visual and auditory stimulation. Using the glasses, 8 of 15 patients achieved a meaningful benefit in walking speed of 21.5% (95% CI 3.9%). A further two patients had subjective benefit. It was found that both visual and auditory cues were beneficial, different patterns suiting different patients and more effective in different circumstances. Overall, the best pattern was visual cueing alone with a fixed cue present all the time. This pilot study shows promising improvement in the gait of a significant proportion of Parkinson's disease patients through the use of a simple, inexpensive and robust design of walking glasses, suggesting practical applicability in a therapy setting to large numbers of such patients.